Mutations in COA3 cause isolated complex IV deficiency associated with neuropathy, exercise intolerance, obesity, and short stature. Issue 3 (20th January 2015) - Ostergaard, Elsebet; Weraarpachai, Woranontee; Ravn, Kirstine; Born, Alfred Peter; Jønson, Lars; Duno, Morten; Wibrand, Flemming; Shoubridge, Eric A; Vissing, John
Abstract : Background: We investigated a subject with an isolated cytochrome c oxidase (COX) deficiency presenting with an unusual phenotype characterised by neuropathy, exercise intolerance, obesity, and short stature. Methods and results: Blue-native polyacrylamide gel electrophoresis (BN-PAGE) analysis showed an almost complete lack of COX assembly in subject fibroblasts, consistent with the very low enzymatic activity, and pulse-labelling mitochondrial translation experiments showed a specific decrease in synthesis of the COX1 subunit, the core catalytic subunit that nucleates assembly of the holoenzyme. Whole exome sequencing identified compound heterozygous mutations (c.199dupC, c.215A>G) in COA3, a small inner membrane COX assembly factor, resulting in a pronounced decrease in the steady-state levels of COA3 protein. Retroviral expression of a wild-type COA3 cDNA completely rescued the COX assembly and mitochondrial translation defects, confirming the pathogenicity of the mutations, and resulted in increased steady-state levels of COX1 in control cells, demonstrating a role for COA3 in the stabilisation of this subunit. COA3 exists in an early COX assembly complex that contains COX1 and other COX assembly factors including COX14 (C12orf62), another single pass transmembrane protein that also plays a role in coupling COX1 synthesis with holoenzyme assembly. Immunoblot analysis showed that COX14 was undetectable in COA3 subject fibroblasts, and that COA3 was undetectable in fibroblasts from a COX14 subject, demonstrating the interdependence of these two COX assembly factors. Conclusions: The mild clinical course in this patient contrasts with nearly all other cases of severe COX assembly defects that are usually fatal early in life, and underscores the marked tissue-specific involvement in mitochondrial diseases.